Maligna esophagus neoplasia: an epidemiological analysis of cases notified in brazil between 2015 and 2019 (Research, Society and Development, 2021)
Esophageal Neoplasia is one of the most common in the world, being classified in the eighth position, in addition to representing the sixth fatality due to cancer, in view of the aggressiveness of the pathological process, the diagnostic difficulty, culminating in its late characteristic and, finally, in poor prognosis due to the association of such factors. This work analyzes epidemiologically the cases of malignant esophageal neoplasia reported in Brazil between the years 2015 and 2019. The qualitative and quantitative research was carried out in the DATASUS database. White ethnicity, male gender, presence of Gastroesophageal Reflux Disease (GERD), smoking and age over 50 years are some risk factors for the appearance of esophageal neoplasms. The diagnosis sometimes happens late, and screening tests have increased risks, such as esophageal perforations, bleeding and others, such as cardiopulmonary events. The increase in life expectancy of the Brazilian population is also a point to be considered in the large number of cases. The highest incidence of malignant neoplasm in the esophagus occurred in the Southeast region, however, an interesting cultural factor, present in the South region (Brazil, must be considered), this being the high consumption of mate herb in the form of mate.